Risk factors for severe COVID-19 in people with cystic fibrosis: A systematic review - Terlizzi, Vito; Motisi, Marco Antonio; Pellegrino, Roberta; Padoan, Rita; Chiappini, Elena (Frontiers in Pediatrics, 2022)
Background: People with cystic fibrosis (CF) are considered a clinically fragile population with an intrinsic higher risk of developing severe COVID-19, though a certain variability in terms of outcomes and hospitalization has been noticed in this population. Aim: To highlight the main risk factors for severe COVID-19 in patients with CF. Methods: A systematic review of the current literature was conducted through PubMed and EMBASE databases. English-written articles reporting clinical data on CF patients with SARS-CoV2 infection were included and analysed. Selected reports were evaluated for adherence to STROBE recommendations. Results: After the selection phase, 9 observational studies were included, 5 of which reported data from CF Registry Global Harmonization Group. The hospitalization rate ranged from 18.2-58.1%. The main risk factors for severe outcome were as follows: FEV1 <70%p, CF-related diabetes, age >40 years, pancreatic insufficiency, underweight, previous transplant, azithromycin use. Use of dornase alfa was associated with decreased risk for severe disease, while there was insufficient evidence to establish the role of inhaled steroids or CFTR modulators. No solid data regarding specific SARS-CoV2 therapies in CF patients emerged. Conclusion: Most people with CF experience a mild course of SARS-CoV-2 infection, nevertheless subgroups with higher risk of severe outcome emerged. Maintenance therapies for CF overall did not show a clear preventive effect against severe outcomes, although dornase alfa seems to give some protection. Due to the current lack of data on specific COVID-19 therapies and immunization in CF patients, further studies are needed to establish their impact in this population.